Strategic Management of The Pancasila Student Profile Strengthening Project (P5) at SMPN 4 Gerung - Miptahul Jannah,; Baiq Rohiyatun,; M. Ary Irawan, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
The Pancasila Student Profile Strengthening Project (P5) is part of the Independent Curriculum (Curriculum Merdeka), designed to shape student character through project-based learning. Its successful implementation is heavily influenced by the school's managerial strategies. This study aims to describe the strategic management of P5 at SMP Negeri 4 Gerung, focusing on the planning, implementation, and evaluation stages. The research employed a qualitative case study approach, with data collection techniques including interviews, observation, and documentation. Informants included the Vice Principal for Curriculum, the P5 Coordinators of grades VII and VIII, and students in grades VII and VIII. The results indicate that strategic planning was carried out collaboratively, adapting themes to student characteristics and the local context. Project implementation took place during specific hours through activities such as eco-briking, election simulations, and local culinary preparation. Evaluation was conducted through student reflection and internal meetings, although not yet optimal. The conclusions of this study confirm that strategic management plays a crucial role in supporting P5 implementation, but further strengthening of teacher training, module development, and evaluation systems is needed to ensure program implementation is more effective and sustainable. Keywords: Strategic Management, P5 Project, Independent Curriculum Abstrak: Proyek Penguatan Profil Pelajar Pancasila (P5) merupakan bagian dari Kurikulum Merdeka yang dirancang untuk membentuk karakter peserta didik melalui pembelajaran berbasis proyek. Keberhasilan pelaksanaannya sangat dipengaruhi oleh strategi manajerial yang diterapkan sekolah. Penelitian ini bertujuan mendeskripsikan manajemen strategik P5 di SMP Negeri 4 Gerung, yang mencakup tahapan perencanaan, pelaksanaan, dan evaluasi. Penelitian menggunakan pendekatan kualitatif jenis studi kasus, dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Informan terdiri dari Wakil Kepala Sekolah Bidang Kurikulum, Koordinator P5 kelas VII dan VIII, serta siswa kelas VII dan VIII. Hasil penelitian menunjukkan bahwa perencanaan strategik dilakukan secara kolaboratif dengan menyesuaikan tema terhadap karakteristik siswa dan konteks lokal. Pelaksanaan proyek dilakukan pada jam khusus melalui kegiatan seperti ecobrik, simulasi pemilu, dan pengolahan kuliner lokal. Evaluasi dilaksanakan melalui refleksi siswa dan rapat internal, meskipun belum berjalan secara optimal. Simpulan dari penelitian ini menegaskan bahwa manajemen strategik berperan penting dalam mendukung implementasi P5, namun masih diperlukan penguatan dalam pelatihan guru, penyusunan modul, dan sistem evaluasi agar pelaksanaan program lebih efektif dan berkelanjutan. Kata Kunci: Manajemen Strategik, Proyek P5, Kurikulum Merdeka.